2023
DOI: 10.3389/fmars.2022.1072391
|View full text |Cite
|
Sign up to set email alerts
|

Effects of exogenous hormones on the regeneration of juveniles from Sargassum fusiforme holdfasts

Abstract: During the cultivation of Sargassum fusiforme, sexual reproduction of superior strains can hinder the stable inheritance of their desirable traits and reduce their economic benefits. However, vegetative reproduction of S. fusiforme holdfasts has high potential for subculture. In this study, we investigated the effects of different concentrations of α-naphthaleneacetic acid (NAA), gibberellin (GA3), and 6-benzyladenine (BAP) on the growth and regeneration of S. fusiforme holdfasts. Exogenous application of 1.5,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…We observed that the callus-like/adventitious bud induction rate and number of bud per explant varied widely among explants from different parts of S. fusiforme after tissue culture. The holdfasts and stems of S. fusiforme can serve as primary materials for tissue culture (Luo et al, 2023). Different parts of the stems were cultivated in groups, with adventitious buds more easily induced near the upper stem tip than near the stem base, possibly because S. fusiforme is polarized, similar to other macroalgae.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We observed that the callus-like/adventitious bud induction rate and number of bud per explant varied widely among explants from different parts of S. fusiforme after tissue culture. The holdfasts and stems of S. fusiforme can serve as primary materials for tissue culture (Luo et al, 2023). Different parts of the stems were cultivated in groups, with adventitious buds more easily induced near the upper stem tip than near the stem base, possibly because S. fusiforme is polarized, similar to other macroalgae.…”
Section: Discussionmentioning
confidence: 99%
“…However, the traditional method of seedling cultivation leads to the growth of weed algae, which compete with seedlings for nutrients and space, and it is challenging to control the temperature, pH, and light. Even during sexual reproduction, it is difficult to stabilize the inheritance of some heat-and cold-tolerant strains because of crossbreeding (Chen and Zou, 2014;Chen et al, 2019;Luo et al, 2023). Traditional seedling culture conditions are complicated and time-consuming, and the maintenance and replacement of cultivation equipment during cultivation can cause a serious economic burden (Largo et al, 2020;Collins et al, 2022;Arbaiza et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Exogenous application of α-naphthaleneacetic acid (NAA), gibberellin (GA3), and 6-benzyl adenine (BAP) has been used to induce regeneration of Sargassum fusiforme to obtain more regenerative seedlings within a short time, thereby improving economic efficiency [208]. Plant growth hormone (zeatin + phenylacetic acid) has been used for micropropagation in three color morphotypes of Kappaphycus alvarezii var.…”
Section: Perspectivesmentioning
confidence: 99%